Improving the Lot of the Farmer: Development Challenges in Timor-Leste during the Second Decade of Independence - Mats Lundahl; Fredrik Sjöholm (Research Institute of Industrial Economics (IFN), 2012)
Timor-Lestes first ten years of independence have been turbulent and a large share of the population remains poor. Broad-based improvements in living standards will require improvements in agricultural production since most Timorese are subsistence farmers and since there is no modern sector to absorb a fast-growing population. This paper discusses what determines agricultural development in Timor-Leste and how such development can be achieved. This is done in two steps. The first one takes the production function as its point of departure. Agricultural output is seen as a function of inputs (land, capital and labor) and technology, which in turn are influenced by the infrastructure and institutions of the economy and by external factors which cannot be influenced by policy measures. The second part, in turn, emphasizes the fact that Timor-Leste is a market economy. A model of an agricultural household is constructed. The static optimum of the household is derived and the effects on production, consumption, sales, income and leisure of the household of different price incentives (changes in food prices, cash crop prices and prices of manufactured goods) are investigated.
Keywords: O13; Q15; Q18; 330; Timor-Leste; Agriculture; Poverty; Development; Rural